Effects of mangrove forest on the biodiversity of macrobenthos under the condition of severe water pollution. Issue 7 (27th November 2014) - Qiu, Guo Yu; Zhou, Fufang; Shi, Xiuhua
Abstract Although it is clear that mangrove (MG) forests have a positive effect on macrobenthos diversity in wetland ecosystems, these effects are not very clear under the condition of severe water pollution. The objective of this study is to investigate the effects of MG forests on macrobenthos diversity under severe water pollution in Shenzhen Bay, where water quality is strongly affected by industry and urbanization. For this purpose, we carried out a field study from December 2009 to July 2011 in the MG wetland in Shenzhen Bay, the only MG wetland located near a metropolis in mainland China. Samples were taken monthly from four habitats, namely, a reed fish pond, Gei wai ponds, mudflats and an MG forest. The results show that the seawater in all four habitats is severely polluted, and the total N, NO3‐N, total phosphate, Cd, Pb and chemical oxygen demand are well over the Chinese national class IV level. The high level of organics (chemical oxygen demand and soil organic matter) and nutrients (nitrate nitrogen) has a significant positive influence (P < 0.05) on the density and biomass of macrobenthos but a negative influence (P < 0.05) on the diversity of the macrobenthos community. Despite the fact that the levels of organics and nutrients were also high in the MG habitat, the species biodiversity was also the most abundant of the four investigated habitats. This suggests that MG habitats have a remarkable positive effect on maintaining biological diversity compared with other habitats. Therefore, we suggest that efforts should be made to strengthen the protection of MG forests to maintain their biological diversity and promote a healthy ecological system. Copyright © 2014 John Wiley & Sons, Ltd.